Interactive Data Visualization with Python Present Your Data As an Effective and Compelling Story, 2nd Edition. - Belorkar, Abha (Packt Publishing, Limited, 2020)
Interactive Data Visualization with Python sharpens your data exploration skills, tells you everything there is to know about interactive data visualization in Python, and most importantly, helps you make your storytelling more intuitive and persuasive.